2015
DOI: 10.1007/s00595-015-1279-z
|View full text |Cite
|
Sign up to set email alerts
|

Annular dynamics after mitral valve repair with different prosthetic rings: A real-time three-dimensional transesophageal echocardiography study

Abstract: Although mitral regurgitation was well controlled by all of the types of rings that were utilized in the present study, we demonstrated that the annulus motion and annulus shape differed according to the type of prosthetic ring that was used, which might provide important information for the selection of an appropriate prosthetic ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Annular sphericity increases with annular dilatation to a more circular-shaped annulus compared with that in a nondilated ellipsoid annulus. 23,24 We found the mean annular sphericity index to be decreased to 0.77 after MVR, which correlates with the 3:4 ratio of our most frequently implanted CE Physio annuloplasty ring (annular sphericity index of 0.75). Moreover, the end-systolic AHCWR also decreased from 0.19 to 0.12, showing no significant changes throughout the cardiac cycle after MVR.…”
Section: Annular Dimensions and Shapesupporting
confidence: 60%
“…Annular sphericity increases with annular dilatation to a more circular-shaped annulus compared with that in a nondilated ellipsoid annulus. 23,24 We found the mean annular sphericity index to be decreased to 0.77 after MVR, which correlates with the 3:4 ratio of our most frequently implanted CE Physio annuloplasty ring (annular sphericity index of 0.75). Moreover, the end-systolic AHCWR also decreased from 0.19 to 0.12, showing no significant changes throughout the cardiac cycle after MVR.…”
Section: Annular Dimensions and Shapesupporting
confidence: 60%
“… Case series, prospective observational study 22 Comparative Ender et al (2010) 54 Germany Patients with MR, pathology not disclosed. Case series, prospective observational study 110 Non-comparative Grapsa et al (2015) 39 USA, UK Patients with degenerative MV disease. Case series, prospective observational study 64 Non-comparative Guo et al (2018) 52 China Patients with degenerative MV disease.…”
Section: Resultsmentioning
confidence: 99%
“…Preoperative angiographic data were used to determine the coronary dominance type. Grapsa et al (2015) 39 Assessed the papillary muscle strain as a contributor to recurrent MR after MV repair for FED. Prospective study.…”
Section: Resultsmentioning
confidence: 99%
“…Early results with the Memo 3D have been previously reported [24]. In addition, Nishi and colleagues [13] and Ryomoto and colleagues [25] demonstrated that after Memo 3D implantation, movement of the anterior and posterior annulus, as well as changes in the mitral annulus throughout the cardiac cycle, is preserved. Wan and colleagues [26] published data of 34 patients treated with the Memo 3D ReChord and compared these data with 32 patients with the Memo 3D.…”
Section: Commentmentioning
confidence: 92%
“…This semirigid ring contains an elastic nitinol and titanium alloy core that proved to accommodate the anatomic saddle shape of the mitral valve annulus and to restore the physiologic diameter ratio [13]. The core is enclosed in a sewing ring made of silicone and polyester fabric.…”
Section: Annuloplasty Devicementioning
confidence: 99%